Perempuan Gerwani Minangkabau dalam Belitan Konflik G30S/PKI 1965 - Serli Agustina; Siti Fatimah (Jurusan Sejarah FIS UNP, 2020)
This article is a historical study that discusses the fate of the Gerwani Minangkabau woman in the conflict wrought by the G30S/PKI 1965. The pupose of this study is to describe the life experiences and the fate of the Minangkabau members of the Gerwani who became entangled in the conflict of their involvement in the illegal organization. This research uses the historical methods based on the four steps of activity of heuristic, source criticism, interpretation and historiography. The conclusion obtained is that this study expounded facts related to the events of the G30S in 1965 that occurred in the land of Minang (west Sumatera). The participation of Minangkabau women in the Gerwani membership dragged them into a conflict that occurred during the events of the G30S 1965. Their desire to fight for women comes to their misery. Discrimination and negative stigma have not stopped them from feeling.